The Relevance of Pragmatism-Based Teaching Methods in Optimizing Information Processing in Primary School Students - Anggraeni Anggraeni; Ana Andriani (Proceedings Series on Social Sciences & Humanities, 2025)
Education is no longer seen merely as a transmission of knowledge from teachers to students, but as an interactive and dynamic process in which students are positioned as active learners. Progressive teaching methods rooted in the philosophy of pragmatism emphasize experiential learning, contextual engagement, and democratic classroom practices. These principles are strongly aligned with Indonesia’s “Merdeka Curriculum”, which promotes learner autonomy and interest-based education. Furthermore, understanding how students process information through attention, encoding, storage, and retrieval is central to developing effective instructional strategies. This article discusses the theoretical foundations of pragmatism in teaching, practical applications in primary education, challenges in implementation, and how information processing theory informs and optimizes these methods to enhance students’ critical thinking and creativity.